A Case of Locally Advanced Well-Differentiated Fetal Adenocarcinoma of the Lung Treated with Concurrent Chemoradiation Therapy - Kyung, Chanhee (The Korean Academy of Tuberculosis and Respiratory Diseases, 2013)
Fetal adenocarcinoma is a rare adenocarcinoma subtype of pulmonary blastoma. A 48-year-old male patient is being referred to our hospital due to progressive dyspnea. A chest X-ray showed a lung mass of unknown origin that was obstructing the right main bronchus. After relieving the airway obstruction with stent insertion via bronchoscopy, a diagnosis of fetal adenocarcinoma is being confirmed through thoracoscopic biopsy. Due to the locally advanced state of the lung cancer, it seemed to be inoperable, and concurrent chemo-radiation therapy was being administered with docetaxel. The stent was removed after improvements in the airway obstruction followed by a lung mass shrinkage. Comparing to other contexts which describe fetal adenocarcinoma as lower grade malignancy with low-associated mortality, herein, we describe a case of locally-advanced fetal adenocarcinoma (T4N3M0). This is the first documented case being treated with concurrent chemoradiation therapy. The followed-up image studies represent a partial response and the patient is currently under further observations.